Simultaneous cooling of the internal and external degrees of freedom of a levitated micromagnet in a cavity magnomechanical system - Lei Chen; Yang Liu; Liang Bin; Sai-Yun Ye; Zhi-Rong Zhong (Physical Review Research)
Cooling the internal and external degrees of freedom (DOFs) of a massive mechanical system close to the quantum ground state is a prerequisite for the quantum manipulation of macroscopic mechanical devices. In this paper, we propose a approach to simultaneously cool both the internal and external DOFs (phonon and center-of-mass modes) of a levitated micromagnet within a cavity magnomechanical (CMM) system. By driving the cavity mode and magnon mode on their respective red sidebands with microwave fields, the proposed scheme effectively suppresses Stokes scattering and significantly enhances the net cooling rate. Moreover, differing from conventional CMM systems, our proposal can achieve simultaneous cooling of the internal and external DOFs even in the unresolved-sideband regime. Our numerical simulations demonstrate the robustness and effectiveness of the scheme by analyzing average occupancies of the internal and external DOFs, as well as identifying the optimal cooling conditions. The proposed scheme establishes a foundation for probing and manipulating the internal DOFs by controlling the external DOFs, which may open additional possibilities for studying nonequilibrium quantum mesoscopic physics.